Analysis of Sandwich Core Fiber Composite Subjected to Different Skin Reinforcement Materials - Burhan, Muhammad Burhanuddin bin Mohd Mazlan; Mohd Nazrul Roslan (Progress in Engineering Application and Technology, 2021)
The aim of this project is to determine the analysis of sandwich core fiber composite subjected to different skin reinforcement materials. A typical composite material is a system of materials composing of two or more materials (mixed and bonded) on a microscopic scale. Generally, a composite material is composed of reinforcement (fibers, particles, flakes, and/or fillers) embedded in a matrix. This study will be using an aluminum, plastic and steel that act as the skin reinforcement. In order to get the composite material, bamboo fiber is been chosen to be impregnated into the reinforcement with the aid of epoxy that act as a resin. The sample will be cut into dimension of ten centimeters times ten centimeters. Once the samples become a composite, it will undergo compression testing to obtain the curve line behaviors, maximum force and total energy absorption